High‐Resolution Magnetic‐Geochemical Mapping of the Serpentinized and Carbonated Atlin Ophiolite, British Columbia: Toward Establishing Magnetometry as a Monitoring Tool for In Situ Mineral Carbonation - Masako Tominaga; Andreas Beinlich; Eduardo A. Lima; Paiden Pruett; Noah R. Vento; Benjamin P. Weiss (Geochemistry, Geophysics, Geosystems, 2023)
Abstract We address in situ serpentinization and mineral carbonation processes in oceanic lithosphere using integrated field magnetic measurements, rock magnetic analyses, superconducting quantum interference device (SQUID) microscopy, microtextural observations, and energy dispersive spectroscopy phase mapping. A representative suite of ultramafic rock samples were collected, within the Atlin ophiolite, along a 100‐m long transect across a continuous outcrop of mantle harzburgite with several alteration fronts: serpentinite, soapstone (magnesite + talc), and listvenite (magnesite + quartz). Strong correlations between changes in magnetic signal strengths and amount of alteration are shown with distinctive contrasts between serpentinite, transitional soapstone, and listvenite that are linked to the formation and breakdown of magnetite. While previous observations of the Linnajavri ultramafic complex indicated that the breakdown of magnetite occurred during listvenite formation from the precursor soapstone (Tominaga et al., 2017, https://doi.org/10.1038/s41467-017-01610-4), results from our study suggest that magnetite destabilization already occurred during the replacement of serpentinite by soapstone (i.e., at lower fluid CO2 concentrations). This difference is attributed to fracture‐controlled flow of sulfur‐bearing alteration fluid at Atlin, causing reductive magnetite dissolution in thin soapstone zones separating serpentinite from sulfide‐mineralized listvenite. We argue that magnetite growth or breakdown in soapstone provides insight into the mode of fluid flow and the composition, which control the scale and extent of carbonation. This conclusion enables us to use magnetometry as a viable tool for monitoring the reaction progress from serpentinite to carbonate‐bearing assemblages in space and time with a caution that the three‐dimensionality of magnetic sources impacts the scalability of measurements.